Smectic, columnar and cubic mesophases in binary systems of hemiphasmidic and calamitic amphiphilic diols - SAUER, CHRISTIANE; DIELE, SIEGMAR; LINDNER, NIELS; TSCHIERSKE, CARSTEN (Liquid crystals, 1998)
A first example of an amphiphilic hemiphasmid consisting of a biphenyl rigid core connected to a hydrophilic 5,6-dihydroxy-3-oxahexyloxy group at one end and carrying two lipophilic dodecyloxy chains at the other end has been synthesized by a Pd-catalysed cross coupling reaction. The liquid crystalline properties of this compound have been investigated by polarized light microscopy, by differential scanning calorimetry and by X-ray diffraction. It exhibits a thermotropic hexagonal columnar mesophase which is stabilized on addition of formamide. On addition of ethylene glycol, a bicontinuous cubic mesophase is induced. Furthermore, binary mixtures of this compound with structurally related single chain amphiphiles have been investigated. Besides a smectic A phase, an induced columnar mesophase and a cubic phase were found in these mixtures.